Survival and Opportunity: Self-Employment Among Women Heads of Families in Mato Grosso’s Agribusiness and Traditional Sectors (Global Journal of Management and Business Research, 2025)
I Introduction F or most of the population of pre-industrial societies there was no separation between productive activities and domestic activities Work was carried out at home or in its vicinity This situation changed with the advent of modern industry which caused a separation between the home and the workplace Giddens 2005 Nolan Lenski 2015 With the development of the industrialization process of societies there was a separation between the home and the workplace making them distinct spheres the public and the private Men who carried out their work outside the home began to participate more in the public sphere while many women remained in the private sphere in the domestic sphere linked to the tasks of taking care of the house and children